Development of Simple Boyle's Law Practicum Equipment to Train Science Process Skills - Hakim, Luqman; Herlina, Kartini; Anggreini, Anggreini; Abdurrahman, Abdurrahman (JIPF (Jurnal Ilmu Pendidikan Fisika), 2024)
This research aims to develop a simple Boyle's law practicum equipment that can be used to train science process skills in learning the concept of Boyle's law in schools. This research uses the Design and Development Research development model adapted from Richey and Klien with stages namely analyze, design, development, and evaluation.. The practicum equipment developed is declared feasible to use if it has passed the validity test and practicality assessment.. The validity test obtained a percentage of 88% with a very valid category.. Practicality assessment is represented through teacher perception, students response, and analysis of science process skills.. The results of teacher perception obtained a percentage of 83% with a very practical category. The results of students' responses obtained a percentage of 90% with a very practical category. The analysis of science process skills obtained a percentage of 87% with a very good category. Based on the validity test and practicality assessment that has been carried out, it can be concluded that the practicum equipment developed is suitable to be applied to train science process skills in learning the concept of Boyle's law in schools.